ANALISIS PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DI DESA NEGERI GUGUNG SIBOLANGIT - Putra, M Alief Kurniadi; -, Hamdani (Power Elektronik : Jurnal Orang Elektro, 2024)
The Micro-Hydro Power Plant (PLTMH) is a small-scale hydropower generator with an installed capacity of less than 200 kW. It utilizes the flow of water from irrigation channels, rivers, or natural waterfalls by harnessing the available waterfall height at the construction site. This study focuses on the planning techniques and equipment required for PLTMH located in rural areas such as Negeri Gugung Sibolangit to meet the electricity needs of the residents. The research includes a technical feasibility study by surveying the hydrological potential and the potential falling height (head) at the planned PLTMH development site. Based on the calculations, the electricity demand for the residents of Negeri Gugung Sibolangit during peak load is estimated to be 20 kW. Field surveys indicate that the potential water discharge in the river of Negeri Gugung Sibolangit is approximately 0.95 m3/s, with a planned water discharge in the diversion channel of 0.38 m3/s and a waterfall height of 7.5 meters. This configuration can generate a power of 28 kW, which is sufficient to meet the needs of the local population. Considering the head, planned discharge, and installed capacity, the suitable turbine type is determined to be a cross-flow turbine, and the generator type is identified as a synchronous generator. Based on these parameters, it can be concluded that building a PLTMH in Negeri Gugung Sibolangit is highly feasible.